A new hadrosauroid dinosaur from the early late cretaceous of Shanxi Province, China. - Run-Fu Wang (Public Library of Science (PLoS), 2013)
Background The origin of hadrosaurid dinosaurs is far from clear, mainly due to the paucity of their early Late Cretaceous close relatives. Compared to numerous Early Cretaceous basal hadrosauroids, which are mainly from Eastern Asia, only six early Late Cretaceous (pre-Campanian) basal hadrosauroids have been found: three from Asia and three from North America. Methodology/principal findings Here we describe a new hadrosauroid dinosaur, Yunganglong datongensis gen. et sp. nov., from the early Late Cretaceous Zhumapu Formation of Shanxi Province in northern China. The new taxon is represented by an associated but disarticulated partial adult skeleton including the caudodorsal part of the skull. Cladistic analysis and comparative studies show that Yunganglong represents one of the most basal Late Cretaceous hadrosauroids and is diagnosed by a unique combination of features in its skull and femur. Conclusions/significance The discovery of Yunganglong adds another record of basal Hadrosauroidea in the early Late Cretaceous, and helps to elucidate the origin and evolution of Hadrosauridae.